Comparison of DNA Isolation Methods that Derived from Leaves of a Potential Anti-Cancer Rodent Tuber (Typhonium flagelliforme) Plant - Gemilang Rahmadara; Nurul Fitri Hanifah; Rismayanti Rismayanti; Devit Purwoko; Andi Rochandi; Teuku Tajuddin (International Journal of Agriculture System, 2022)
The content of polysaccharides, polyphenols, proteins, and RNA compounds is the main problem often found in Plants DNA isolation, which inhibit the process of DNA isolation. Comparing the methods of plant DNA isolation is necessary for obtaining the DNA with good quality, purity, high concentration and efficiency time and cost. This study aimed to determine the best DNA isolation method that derived from leaves of a potential anti-cancer Rodent Tuber (Typhonium flagelliforme) plant by comparing the conventional DNA isolation method (cetyl trimethyl ammonium bromide/CTAB) and 2 commercial kits (Promega Wizard™ Genomic DNA Purification Kits, and Geneaid Genomic Mini Kit). The results showed that the CTAB method yielded a higher amount of DNA (>100 ng/µL) at the cost of 0.49 USD per sample, in comparison with Promega method (69.19 to 157.68 ng/µL) at 3.28 USD per sample and Geneaid method (8.15 to 18.52 ng/µL) at 2.06 USD per sample. Based on the purity of isolated DNA (A260/280), CTAB method produced relatively similar DNA quality to Promega kit (1.8-2.0). On the other hand, Geneaid method resulted in a lower purity value at 1.15 to 1.60.